Dimerization of Hexadecene with Acid Mesoporous Silica‐Alumina Catalysts. Issue 6 (3rd March 2021) - Kumar, Narendra; Lindblad, Marina; Makkonen, Jaana; Sippola, Väinö; Österholm, Heidi; Tiitta, Marja
Abstract: Catalytic dimerization of 1‐hexadecene is shown to be a promising path to make high quality base oil. The base oil is produced by hexadecene dimerization with acid mesoporous silica‐alumina catalyst, followed by distillation and hydrogenation. The base oil stock had a high viscosity index (typically 140–150) and a low volatility (Noack typically less than 8 %). The best performance in hexadecene dimerization was achieved with the MCM‐22 zeolite embedded MCM‐41 catalyst within the silica‐alumina catalysts compared. Commercial mesoporous silica‐alumina catalysts behaved similarly to a non‐commercial MCM‐41 catalyst. Y‐zeolite and ion exchange resin Amberlyst‐35 deactivated fast. Abstract : A promising pathway to produce a high quality base oil by n ‐hexadecene dimerization is discussed. The acid mesoporous silica‐alumina catalysts showed a remarkable activity in the dimerization delivering conversions of hexadecene above 50 % at reaction temperature 120 °C. The base oil produced from dimerization products after the distillation and hydrogenation has excellent properties.